Penerapan Ice Breaking untuk Meningkatkan Minat Belajar Mahasiswa PGSD UMN Al Washliyah - Nila Lestari; Khairina Ulfa Syaimi; Nurmairina Nurmairina (Departement of Mathematics Education, 2023)
This study aims to increase the learning interest of PGSD UMN AL Washliyah students in the subject of Learning Problems in Elementary School. This type of research is class action research (PTK) with descriptive qualitative data presentation. The research instrument is a questionnaire sheet of student learning interest and essay test questions, This research was conducted for 2 cycles in each cycle consisting of 2 meetings, the results of this study were In cycle 1 for indicators of feeling happy about learning obtained an average percentage of 78.78%, on indicators of attention and thoughts focused on learning obtained an average percentage - an average of 44.45%, for the indicator of having a willingness to learn an average percentage of 33.33%, for the indicator of feeling that one has to be active in learning an average percentage of 57.57% is obtained, for the indicator of realizing the desire to learn a percentage of 75 is obtained, 75% and for cycle 2 indicators feel happy about dip learning obtained an average percentage of 100%, the indicators of attention and thinking focus on learning obtained an average percentage of 84.84%, the indicator of having a willingness to learn obtained an average percentage of 90.90%, the indicator of feeling that one must be active in learning obtained the average percentage is 81.81%, the indicator of realizing the desire to learn is a percentage of 100%. From the questionnaire data obtained in cycle 2, the researcher saw an increase in the learning interest of PGSD UMN Al Washliyah students. This was proven in cycle 2, the achievement of each indicator had reached the minimum criteria of 75%, thus concluding that the application of Ice Breaking could increase the learning interest of PGSD UMN Al students. Washliyah in the subject of Learning Problems in Elementary School, for other supporting data, namely the completeness of learning outcomes in cycle 1 reaches 69.7% and the completeness of learning outcomes in cycle 2 reaches 97.97% so that there is an increase in learning outcomes from cycle 1 to cycle 2 reaching 28.27%.